Comparing the Effectiveness of Vitamin B6 and Ginger in Treatment of Pregnancy-Induced Nausea and Vomiting - Ezzatalsadat Haji Seid Javadi; Fatemeh Salehi; Omid Mashrabi (Obstetrics and Gynecology International)
Objective. Comparing the effectiveness of vitamin B6 (40 mg twice daily) and ginger (250 mg four times daily) in treatment of pregnancy nausea. Methods. In a clinical trial in health centers of Qazvin University of Medical Sciences from November 2010 to February 2011 on pregnant mothers, the effects of vitamin B6 (40 mg twice daily) and ginger (250 mg four times daily) were evaluated in treatment of pregnancy nausea. Results. In both groups, treatments with vitamin B6 or ginger led to significant reduction in MPUQE score. Scores of symptoms at the day before treatment in vitamin B6 and ginger groups were and , respectively, and reduced to and , respectively, in the fourth day of treatment; however, mean changes in the two groups were not significantly different. Mean changes of MPUQE score in ginger and vitamin B6 groups were and , respectively, showing no significant difference (). Conclusion. Vomiting was more reduced in vitamin B6 group; however, this reduction was not statistically significant. There was no significant difference between the two groups in nausea occurrences and their duration. No side effect was observed in either group.